Mexican Americans Participate in Research More than Expected while non-Hispanic Whites Participate Less than Expected. - Gonzales, Xavier F. (Journal of Health Care for the Poor & Underserved, 2022)
Objective. To identify Hispanic/Latinx and non Hispanic White participation rates in a community-based project using door-to-door recruitment. Methods. We conducted a two-stage area probability sample of housing units in Nueces County, Texas, using Census data including Mexican Americans (MAs) and non-Hispanic Whites (NHWs). From May 2018–February 2020, residents over 64 were asked to take a cognitive screen. We compared expected and observed ethnic-specific participation. Results. Nearly a thousand (996) participants enrolled. Accounting for sampling error, the observed count of MAs (n=609) significantly exceeded expectations ([inline-graphic 01], [95% CI: 521,542]). The observed count of NHWs (n=387) was less than expected ([inline-graphic 02], [95% CI: 455, 473]. The sub-group with the largest difference in observed vs. expected participants was MA women, n=376 observed, 306 (95% CI: 300, 312) expected. Conclusions. Mexican Americans were significantly more likely to participate than expected, challenging the notion that ethnic minority populations are less likely to agree to research.